The Language Attitude of Madurese Speakers in Jember: The Sociolinguistic Identity of a Multilingual Community - Hasan Suaedi; Fitri Amilia; Yeni Mardiyana Devanti; Astri Widyaruli Angraeni; Nurkamilah Nurkamilah; Indah Werdiningsih (Universitas Muhammadiyah Malang, 2025)
Language attitude refers to the behavior of speakers toward a language and its usage. There are differences in the language attitudes of Madurese speakers on Madura Island and those in Java. These differences arise from cultural contact among language speakers. This study aims to explore the language attitudes of Madurese speakers in Jember. Jember is a regency characterized by harmonious cultural interactions. Many residents in Jember are multilingual, speaking Indonesian and two regional languages: Javanese and Madurese. This research employs a phenomenological approach to capture the language attitudes of Madurese speakers in Jember as a representation of a multilingual society. The data were gathered through indicators of language attitudes using a questionnaire distributed via Google Forms. The respondents targeted were Madurese speakers with varied educational backgrounds, balanced in terms of gender. The questionnaire covered aspects such as comprehension, usage, preservation, and transmission of the Madurese language in their surroundings. The data were analyzed descriptively to identify the language attitudes of Madurese speakers. The analysis revealed both positive and negative attitudes. Positive attitudes were marked by comprehension, usage, preservation, and transmission of the Madurese language within families and local communities. Positive attitudes were evident in private and public settings, demonstrating pride in the language and its use. On the other hand, negative attitudes were also observed. These included partial pride in the Madurese language—speakers were willing to use the language but reluctant to preserve or pass it down to their children. Some speakers used the language but resisted being labeled as Madurese. The key finding of this study is the distinction between the language attitudes of Madurese speakers on Madura Island and those outside it. Madurese speakers on Madura Island are primarily monolingual or bilingual (Madurese and Indonesian). At the same time, those outside the island often belong to multilingual communities and display a complex sense of pride in multiple languages. Multilingual Madurese speakers often identify themselves as